Karush-Kuhn-Tucker Optimality Conditions and Duality for Multiobjective Semi-Infinite Programming Via Tangential Subdifferentials. (25th April 2020) - Tung, Le Thanh
Abstract: The aim of this article is to study Karush-Kuhn-Tucker optimality conditions and duality for nonsmooth multiobjective semi-infinite programing (MSIP). By using tangential subdifferentials and suitable generalized constraint qualifications, we establish necessary and sufficient optimality conditions for some types of efficient solutions of the MSIP. We also propose Wolfe and Mond-Weir type duality for the MSIP and explore weak and strong duality relations under generalized convexity.